The Effect of Fieldwork Practices, Information on the World of Work and Motivation to Enter the World of Work on Job Readiness - Kailan, Fikri; Pujiati, Pujiati; Suroto, Suroto; Winatha, I Komang; Rahmawati, Fanni (Economic Education and Entrepreneurship Journal, 2024)
A workforce with professional competence is a need for market share in the current era. This effort can be taken through the world of education, one of which is by implementing fieldwork practices. This study aims to determine the effect of fieldwork practices, information on the world of work, and motivation to enter the world of work on job readiness. The research method uses descriptive verification with ex post facto approach and survey. The population in the study was class XII students majoring in marketing SMKN 4 Bandar Lampung with non-probability sampling techniques. Data collection techniques with questionnaires, interviews, and documentation. SPSS software-assisted testing and data processing. The results of this study show that there is an influence of fieldwork practices, information on the world of work, and motivation to enter the world of work on the job readiness of class XII students of SMK Negeri 4 Bandar Lampung. Learners can integrate real experience with formal Education that provides in-depth knowledge of job demands while encouraging motivation and job readiness.Keywords: Fieldwork Practices, Information on the World of Work, Job Readiness, Motivation to Mask the World of WorkDOI: http://dx.doi.org/10.23960/E3J/v6i2.42-47